Supramolecular trapping of a cationic all-metal σ-aromatic Bi4 ring - Yadav, Ravi; Maiti, Avijit; Schorpp, Marcel; Graf, Jürgen; Weigend, Florian; Greb, Lutz (Nature chemistry, 2024)
Aromaticity in organic molecules is well defined, but its role in metal-only rings remains controversial. Here we introduce a supramolecular stabilization approach of a cationic Bi4 rhomboid within the symmetric charge sphere of two bowl-shaped dianionic calix[4]pyrrolato indinates. Crystallographic and spectroscopic characterization, quantum chemical analysis and magnetically induced ring currents indicate σ-aromaticity in the formally tetracationic 16-valence electron [Bi4]4+ ring. Computational screening for other p-block elements identifies the planar rhomboid as the globally preferred structure for 16-valence electron four-atomic clusters. The aromatic [Bi4]4+ is isoelectronic to the [Al4]4−, a motif previously observed as antiaromatic in Li3[Al4]− in the gas phase. Thus, subtle factors such as charge isotropy seem to decide over aromaticity or antiaromaticity, advising for caution in debates based on the Hückel model—a concept valid for second-row elements but less deterministic for the heavier congeners.
Im Titel ist die Zahl "4" tiefgestellt
Gesehen am 01.07.2024